Isolated acute sphenoid sinusitis presenting with hemicranial headache and ipsilateral abducens nerve palsy. (8th June 2015) - Gupta, Rahul; Shukla, Rakesh; Mishra, Anupam; Parihar, Anit
Abstract : Isolated sphenoid sinusitis is a rare disorder and may present with complications due to its anatomical location and proximity to the intracranial and orbital contents. It is frequently misdiagnosed, because the sphenoid sinus is not visualised adequately with routine sinus radiographs and is not accessible to direct clinical examination. We report a case who presented with hemicranial headache and ipsilateral abducens nerve palsy as the presenting feature of sphenoid sinusitis. The symptoms disappeared within a week of conservative treatment. Sphenoid sinusitis should be kept in the differential diagnosis of isolated sixth cranial nerve palsy, especially in the presence of headache, and all patients should be investigated with CT/MRI brain. Prompt diagnosis and management before intracranial extension can prevent devastating complications.